Pembelaan Jalal Al-Din Al-Suyuti Atas Kritik Ibn Jauzi Terhadap Hadis Sunan Abi Daud - huda, ikmal tahjibil; Muhid; Baitul Hantira (Kartika: Jurnal Studi Keislaman, 2026)
This research explores Ibn Jauzi's criticism of the hadiths in Abu Dawood's Sunan, followed by al-Suyuti's defense. The hadiths deemed maud'u (fabricated) by Ibn Jauzi are documented in his work titled "al-Maudu’at libni al-Jauzi," which is then refuted by al-Suyuti in his writing titled "Alai al-Manu’ah Fi al-Ahadithu al-Maudu’ah." The research methodology employed is literature study, where all information is derived from relevant written sources directly or indirectly related to the topic. The selected hadiths for the study are referenced from their original sources. After conducting the analysis, the researcher identified several hadiths in Sunan Abu Dawood deemed maud'u or false according to Ibn Jauzi, and these criticisms are countered by al-Suyuti in his work "Alai al-Manu’ah Fi al-Ahadithu al-Maudu’ah." Based on the research findings, Ibn Jauzi critiques hadiths in Sunan Abu Dawood, focusing on a maud'u hadith involving three chains, including Ibn Abbas, with errors in the chain, strengthened by Imam Zarkashi. The second criticism relates to the inauthenticity of the hadith due to the involvement of the narrator 'Ammar, whom Ibn Jauzi accuses of lying. Al-Suyuti defends this hadith, stating that 'Ammar did not narrate it personally, and there are other chains supporting its validity. Al-Suyuti's third response indicates that Imam Bukhari also narrated the hadith, even including it in the chapter on etiquette in "al-Adab al-Mufrad," acknowledging its authenticity.